Borders and boundaries in Northern Ireland and the poetry of Seamus Heaney - Moi, Ruben (Nordlit, 2014)
This essay discusses the borders and boundaries between the poetry of Seamus Heaney, the 1995 Nobel Laureate from Northern Ireland, and the Troubles of the border-riven society from which it stems.